Pengaruh Leverage, Profitabilitas, dan Manajemen Laba Terhadap Tax Avoidance Dengan Ukuran Perusahaan Sebagai Variabel Kontrol - Ashar Rahmanda, Fadel; Yuni Nur Susilowati, Retno (Shofanah Media Berkah, 2024)
This research examines the influence of leverage, profitability, and earnings management on tax avoidance, with firm size as a control variable. The population used in this study consists of manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sample selection was done using purposive sampling, resulting in a sample of 50 companies. The type of data used in this study is secondary data, and the data collection method is documentation. The data analysis method employed is multiple linear regression analysis, which was analyzed using SPSS 25. The results of this study conclude that leverage does not have an effect on tax avoidance. However, profitability and earnings management do have an effect on tax avoidance. This study has limitations, namely in the testing of this research, the sample size was determined using specific criteria (purposive sampling). Additionally, the use of outlier processes in the normality test reduced the amount of data available. The results of this study are expected to enhance understanding and insight regarding tax avoidance and the influence of leverage, profitability, and earnings management on tax avoidance. Additionally, this research is hoped to serve as a consideration for lawmakers in clarifying the provisions in the taxation regulations as stated in Law No. 36 of 2008.